2006
DOI: 10.1002/cmmi.22
|View full text |Cite
|
Sign up to set email alerts
|

CMR 2005: 3.09: Preclinical efficacy of 177Lu‐AMBA, a radiotherapeutic targeting the GRP receptor

Abstract: Tween-20 and injected intravenously into patients with advanced NSCLC. Following intravenous injection of 131 I-labeled NM404 ( < 1 mCi), patients with advanced NSCLC were scanned at 3, 6, 24, 48 and 96 h and at 11 days on a GE Maxxus dual-head SPECT imaging system. Blood and urine samples were collected and analyzed at various times over 7 days and again at 30 days (blood only) after injection of NM404. Results: Initial qualitative imaging results from seven patients indicate that 131 I-labeled NM404 clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…One important prerequisite for effective multiple dose treatment is a fast recovery from receptor downregulation after treatment. Lantry and colleagues (29) found a fast GRP-R recovery within 1 hour after injection, and in the present study we found no decrease in GRP-R density in recurrent tumor disease. Twenty-one days after initial treatment when only small or micrometastatic disease (0-4.3 mm) was apparent, additional 213 Bi-DOTA-PESIN or 213 Bi-AMBA injections reduced the risk of recurrent disease by 57%.…”
Section: Bi-ambasupporting
confidence: 70%
See 2 more Smart Citations
“…One important prerequisite for effective multiple dose treatment is a fast recovery from receptor downregulation after treatment. Lantry and colleagues (29) found a fast GRP-R recovery within 1 hour after injection, and in the present study we found no decrease in GRP-R density in recurrent tumor disease. Twenty-one days after initial treatment when only small or micrometastatic disease (0-4.3 mm) was apparent, additional 213 Bi-DOTA-PESIN or 213 Bi-AMBA injections reduced the risk of recurrent disease by 57%.…”
Section: Bi-ambasupporting
confidence: 70%
“…Radiolabeling of 177 Lu-DOTA-PESIN and synthesis of DOTA-PESIN and AMBA followed procedures described previously (29,31). 213 Bi was eluted from an 225 Ac/ 213 Bi-generator produced by the Institute for Transuranium Elements, Karlsruhe, Germany, using 600 mL 0.1 mol/L NaI/HCl solution (32,33).…”
Section: Peptide Synthesis and Radiolabelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, many common tumors (colon, pancreas, head/ neck, prostate, and lung) may not overexpress somatostatin receptors; however they frequently overexpress Bn receptors, especially the BB 2 receptor Reubi et al, 2002;Moody et al, 2003a;Heuser et al, 2005;Jensen and Moody, 2006;Patel et al, 2006;Fleischmann et al, 2007). This observation has led to considerable interest in the possibility of developing radiolabeled analogs of Bn that could be use for localization of the tumors containing Bn receptors or the development of radiolabeled Bn analogs or Bn analogs coupled to cytotoxic agents that could be used to treat tumors overexpressing Bn receptors through bombesin receptor-mediated cytotoxicity (Breeman et al, 2002;de Jong et al, 2003;Cornelio et al, 2007;de Visser et al, 2007a Tc) GRP analogs with enhanced stability that bind with high affinity to BB 2 receptors have been reported, as well as their ability to image various human tumors in vivo using gamma detectors or positron emission tomography (Breeman et al, 2002;Nock et al, 2003;Smith et al, 2003Smith et al, , 2005Johnson et al, 2006;Lantry et al, 2006;Zhang et al, 2006Zhang et al, , 2007ade Visser et al, 2007a;DimitrakopoulouStrauss et al, 2007;Garrison et al, 2007;Parry et al, 2007;Prasanphanich et al, 2007;Waser et al, 2007). In some preliminary studies in humans, tumors were imaged in the majority of patients, and in some cases, tumors that were not seen with other commonly used imaging modalities were detected using radiolabeled Bn analogs Scopinaro et al, 2004Scopinaro et al, , 2005Dimitrakopoulou-Strauss et al, 2007).…”
Section: Bb 2 Receptor In Diseasesmentioning
confidence: 99%
“…A number of Bn analogs coupled to radiolabeled compounds (e.g., 177 Lu) (Smith et al, 2005;Johnson et al, 2006;Lantry et al, 2006;Zhang et al, 2007a) and to cytotoxic agents (camptothecin, a topoisomerase inhibitor, doxorubicin analogs, and paclitaxel) (Schally and Nagy, 1999;Breeman et al, 2002;Moody et al, , 2006bSchally and Nagy, 2004;Engel et al, 2005;Buchholz et al, 2006;Nanni et al, 2006;Panigone and Nunn, 2006;Safavy et al, 2006;Engel et al, 2007) have been described. These analogs retain their high affinity for Bn receptors and are internalized by Bn receptor-bearing tissues, for the possibility of delivering Bn receptor-mediated tumoral cytotoxicity.…”
Section: Bb 2 Receptor In Diseasesmentioning
confidence: 99%